Effect of dental monomers and initiators on Streptococcus mutans oral biofilms. Issue 5 (May 2018) - Lin, Nancy J.; Keeler, Courtney; Kraigsley, Alison M.; Ye, Jing; Lin-Gibson, Sheng
Graphical abstract: Highlights: Leachables should be considered when designing new dental polymers. Monomers and initiators released from dental polymers can alter biofilms. TEGDMA and BisGMA reduced Streptococcus mutans biofilm metabolic activity at 24 h. CQ stimulated Streptococcus mutans biofilm metabolic activity at 24 h but not at 4 h. Bioactive leachables may be exploited in designing new polymers to reduce tooth decay. Abstract: Objective: Resin-based composites are known to elute leachables that include unincorporated starting materials. The objective of this work was to determine the effect of common dental monomers and initiators on Streptococcus mutans biofilm metabolic activity and biomass. Methods: S. mutans biofilms were inoculated in the presence of bisphenol A glycerolate dimethacrylate (BisGMA), triethylene glycol dimethacrylate (TEGDMA), camphorquinone (CQ), and ethyl 4-(dimethylamino)benzoate (4E) at 0.01 μg/mL up to 500 μg/mL, depending on the aqueous solubility of each chemical. Biofilms were evaluated at 4 h and 24 h for pH ( n = 3–8), biomass via crystal violet ( n = 12), metabolic activity via tetrazolium salt ( n = 12), and membrane permeability for selected concentrations via confocal microscopy ( n = 6). Parametric and non-parametric statistics were applied. Results: 500 μg/mL TEGDMA reduced 24 h metabolic activity but not biomass, similar to prior results with leachables from undercured BisGMA-TEGDMA polymers. 50 μg/mL BisGMA reduced biofilm biomass and activity, slightly delayed the pH drop, and decreased the number of cells with intact membranes. 100 μg/mL CQ delayed the pH drop and metabolic activity at 4 h but then significantly increased the 24 h metabolic activity. 4E had no effect up to 10 μg/mL. Significance: Monomers and initiators that leach from resin composites affect oral bacterial biofilm growth in opposite ways. Leachables, which can be released for extended periods of time, have the potential to alter oral biofilm biomass and activity and should be considered in developing and evaluating new dental materials.